Allelopathic potential of ethanolic extracts and powdered of leaves of Tapirira obtusa on germination and formation of seedlings of different target species (Research, Society and Development, 2021)
The objective was to perform phytochemistry of the leaves of Tapirira obtusa and test your allelopathic potential on germination and seedling formation of three target species. Extracts were used in the concentrations of 25, 50, 100, 150 and 200 mg mL-1, lettuce and tomato seeds; 100 and 200 mg mL-1, sicklepod, in germination chamber being evaluated germination, average germination time, germination speed index and seedling formation. In the vegetation house, powdered leaves proportions of the leaves were used in 0, 5, 10 and 20%, and growth was evaluated. The design was completely randomized, applying variance analysis. Phytochemical analysis revealed high intensity of phenolic compounds and triterpenes and medium intensity of flavonoids and tannins. The extract interfered in germination and growth in the germination chamber and vegetation house with the strong effect allows to suggest its potential for use in the control of unwanted species.